Impact of nanoparticle surface modification on the mechanical properties of polystyrene-based nanocomposites. Issue 20 (20th March 2018) - Kockmann, A.; Porsiel, J. C.; Saadat, R.; Garnweitner, G.
Abstract : A two-step modification strategy is applied to tailor the particle–matrix interface in zirconia nanoparticle–polystyrene composites, achieving strongly enhanced mechanical properties. Abstract : Nanocomposites consisting of metal oxide nanoparticles in a polymeric matrix enable the improvement of material properties and have become highly relevant for numerous applications, such as in lightweight structures with an enhanced Young's modulus for automotive and aircraft applications. The mechanical properties can be adjusted by controlling the amount of particles, their degree of agglomeration and their direct interaction with the matrix. Whilst the latter aspect is particularly promising to achieve high reinforcement at low filler contents, the mechanisms behind this effect are still not fully understood, preventing the rational design of a particle–polymer system with customized properties. In this work, a two-step modification strategy is used to tailor the particle–matrix interface via chemical groups bound to the surface of zirconia nanoparticles. Two modifications featuring terminal vinyl functions as potentially polymerizable groups are compared. Moreover, an inert reference modification is used to determine the influence of the terminal vinylic groups. In contrast to previous studies, all groups are covalently linked to the particle surface, thereby excluding effects such as detachment or weak coordination and ensuring that changes in the mechanical properties can be correlated to chemical groups on the particle surface. After embedding modified particles in polystyrene, the mechanical properties as well as the cross-linkage between the particles and the matrix are characterized, clearly showing the significant impact of a covalent particle–matrix linkage, with an increase of the Young's modulus by up to 28% with only 3 wt% filler content.